Viability and Equilibrium: ISLM Revisited - Jean Cartelier (Levy Economics Institute of Bard College, 1989)
More than fifty years after the publication of Keynes' General Theory and of the review article by Hicks, ISLM remains the basic model for teaching Keynesian macroeconomics. Some Keynesians have rightly insisted on the inadequacies of ISLM in capturing Keynes' thought but have not converted the profession to their views. The same fate may befall this paper whose aim is to suggest an alternative class-room model in the Keynesian and Kaleckian tradition. Nevertheless, in accordance with Orange's lucid motto,"il n'est pas necessaire d'esperer pour entreprendre ni de reussir pour perseverer"... The main thesis is that the concept of static equilibrium, central to ISLM, is not adequate to express the most fundamental aspect of the Keynesian revolution. The first section of the paper is devoted to a defense of the more general concept of viability. Static equilibrium will appear as but one particular example of this larger notion. A very simple model is presented in the second section. Its distinctive feature, aside from its inclusion of the ISLM equations, is to make a clear distinction between the macroeconomic relations exhibiting the consequences of the decisions of the agents on the one hand and the principles according to which these decisions are taken and carried out on the other. The concept of static equilibrium, by contrast is founded on the confusion of the two: a necessary condition for individual actions to be effective is their mutual compatibility. The third section deals very briefly with the implications of the model for the analysis of macroeconomic policy.
Keywords: 330